2006
DOI: 10.1007/s00018-006-6384-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on taste perception

Abstract: Daily experience tells us that temperature has a strong influence on how we taste. Despite the longstanding interest of many specialists in this aspect of taste, we are only starting to understand the molecular mechanisms underlying the temperature dependence of different taste modalities. Recent research has led to the identification of some strong thermosensitive molecules in the taste transduction pathway. The cold activation of the epithelial Na(+) channel and the heat activation of the taste variant of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 49 publications
2
50
0
2
Order By: Relevance
“…A similar progressive effect of cooling at 10° and below was obtained in 2 recent studies of sweet and umami taste (Green and Nachtigal 2015;Green et al 2016). Because bitterness, sweetness and umami are all mediated by C-GPCRs, the thermal sensitivity of TRPM5 (Talavera et al 2005;Talavera et al 2007) must again be considered the possible source of these direct thermal effects. However, the monotonic effect of temperature on the activation of TRPM5 (Talavera et al 2005) suggests that smaller progressive effects of cooling should also occur at 21° and 30°, but no trace of this can be seen at either temperature (Figures 2 and 4).…”
Section: Effects Of Temperature Over Timesupporting
confidence: 67%
“…A similar progressive effect of cooling at 10° and below was obtained in 2 recent studies of sweet and umami taste (Green and Nachtigal 2015;Green et al 2016). Because bitterness, sweetness and umami are all mediated by C-GPCRs, the thermal sensitivity of TRPM5 (Talavera et al 2005;Talavera et al 2007) must again be considered the possible source of these direct thermal effects. However, the monotonic effect of temperature on the activation of TRPM5 (Talavera et al 2005) suggests that smaller progressive effects of cooling should also occur at 21° and 30°, but no trace of this can be seen at either temperature (Figures 2 and 4).…”
Section: Effects Of Temperature Over Timesupporting
confidence: 67%
“…This excitation is transmitted to the brain, where the fi nal representation of each taste modality is formed (Talavera et al, 2007). Increasing the temperature of consumption and the fat content have an inverse eff ect on the ideal sweetening power in whole milk beverages.…”
Section: Resultsmentioning
confidence: 99%
“…There is some suggestion that this phenomenon may be linked to the TRPM5 cation channel, which is a highly temperature-sensitive, heat activated channel, with a key role in the transduction of umami, sweet and bitter taste (Talavera, et al, 2005). It has been further suggested that other tastes, such as salty and sour, perceived by TTs may be linked to the temperature sensitivity of the channels involved in their chemical transduction (Talavera, et al, 2007). Interestingly, TTs do not only have the ability to perceive 'phantom taste' from temperature stimulation, but have also been reported to have a heightened response to taste and some trigeminal stimuli compared to Thermal non-tasters (TnTs) (Green, et al, 2005, Green & George, 2004, Bajec & Pickering, 2008.…”
Section: Introductionmentioning
confidence: 99%